2018
DOI: 10.1093/ajcn/nqy168
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of sugars, saturated fat, and sodium among US children from infancy through preschool age, NHANES 2009–2014

Abstract: The consumption of sugars, fats, and sodium exceeds recommended guidelines before many US children reach school age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 41 publications
6
48
2
1
Order By: Relevance
“…In our study, most food sources of added sugars consumed by young children (2‐5 y) were similar to those eaten by school‐aged children and adolescents, including “soft and fruit drinks” followed by “cakes, cookies, and pies,” “breakfast cereals,” “sweet snacks,” and “milk‐based drinks,” all of them considered ultra‐processed foods. Just as we observed, others have demonstrated that “soft and fruit drinks” consumption is high and is a leading source of added sugars, contributing to approximately one‐third of the added sugars consumed by all children . Due to their substantial contribution to total added sugars intake, previous policy efforts have focused on added sugars from beverages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, most food sources of added sugars consumed by young children (2‐5 y) were similar to those eaten by school‐aged children and adolescents, including “soft and fruit drinks” followed by “cakes, cookies, and pies,” “breakfast cereals,” “sweet snacks,” and “milk‐based drinks,” all of them considered ultra‐processed foods. Just as we observed, others have demonstrated that “soft and fruit drinks” consumption is high and is a leading source of added sugars, contributing to approximately one‐third of the added sugars consumed by all children . Due to their substantial contribution to total added sugars intake, previous policy efforts have focused on added sugars from beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Current added sugars intake in the United States far exceeds national and global guidelines. Young and older children consume on average 14% and 16%, respectively, of total energy intake from added sugars . This is particularly worrying given that a number of studies have linked high consumption of added sugar in early childhood to an increased preference for sweet foods and beverages, dental caries, and excess weight in mid‐childhood and to an increased risk of cardiovascular disease, insulin resistance, type 2 diabetes, and obesity later in life …”
Section: Introductionmentioning
confidence: 99%
“…The use of added salt and sugar intake is inseparably associated with sodium and added/free sugars intake, which also increased with children’s age [ 21 , 22 , 23 , 28 , 37 , 38 , 39 , 40 , 41 ]. Unfortunately, many infants and toddlers around the world have intakes of sodium [ 25 , 26 , 38 , 39 , 42 , 43 ] and added/free sugars [ 22 , 28 , 37 , 39 , 40 , 43 , 44 , 45 ] already close to the upper limit or even above recommendations. Interestingly, many studies conducted on infants and children have shown that boys compared to girls had a higher intake of sodium [ 21 , 23 , 26 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the main food group contributors to nutrient intake is difficult because food groupings often differ between countries. However, in European studies, milk and dairy products, meat and meat products, and oils and fats provide a large contribution to total fat, SFAs, MUFAs, and PUFAs among older children [8,70,71]. By contrast, in the US NHANES 2011-2014 study, for children 2-18 years of age (n = 5876), milk, sweet bakery products, and pizza were the top three food sources of SFAs [72].…”
Section: Contributions Of Food Groups To Fat and Major Fatty Acid Conmentioning
confidence: 93%
“…European data, such as the Identification and Prevention of Dietary-and Lifestyle-Induced Health Effects in Children and Infants (IDEFICS study) of children 2 to 9 years of age from 8 countries, show that the Mediterranean dietary pattern is inversely associated with childhood obesity [6]. Also, in the National Health and Nutrition Examination Survey (NHANES study) 2009-2014, a cross-sectional study of non-breastfeeding American children under 5 years of age, the intake of SFAs was higher than the recommendation (12.8% of TCV) [8]. It should be noted that in NHANES III, the presence of children at home was associated with higher consumption of total fat and SFAs [28] .…”
Section: Introductionmentioning
confidence: 99%